Dietary quality indices and recurrent chronic kidney disease in Taiwanese post-renal transplant recipients - Lin, I-Hsin; Wong, Te-Chih; Duong, Tuyen Van; Nien, Shih-Wei; Tseng, I-Hsin; Wang, Hsu-Han; Chiang, Yang-Jen; Yang, Shwu-Huey (Frontiers in Nutrition, 2023)
Background. This study investigated the association between dietary quality indices and recurrent chronic kidney disease (rCKD) in Taiwanese post renal transplant recipients (RTRs). Methods. This prospective study recruited RTRs aged > 18 years with a functioning allograft and without any acute rejection in the past 3 months from September 2016 to June 2018. Dietary quality indices included Alternative Healthy Eating Index (AHEI) and AHEI-2010, and Taiwanese version of the AHEI (AHEI-Taiwan) were calculated using three-day dietary records, and calculated scores were divided into quartiles. Laboratory data were collected from medical records. rCKD was defined as an estimated glomerular filtration rate (eGFR) of < 60 mL/min/1.73 m2. Logistic regression analysis was performed to analyze the associations. Results. This study included 102 RTRs. The RTRs with higher AHEI, AHEI-Taiwan, and AHEI-2010 scores were older, and had higher eGFRs and lower odds of rCKD. As compared with the lowest quartile, patients with the highest quartiles of the AHEI (Odds ratio, OR, 0.10; 95% confidence interval, 95%CI, 0.02, 0.49; p-trend = 0.004), AHEI-2010 (OR, 0.17; 95%CI, 0.04, 0.72; p-trend = 0.016), and AHEI-Taiwan (OR, 0.13; 95%CI, 0.03–0.59; p-trend = 0.008) had lower odds of rCKD, respectively. As compared with the lowest quartile, patients consumed the highest quartiles of red and processed meat had a 11.43 times higher odds of rCKD (OR, 11.43; 95% CI, 2.30–56.85; p for trend < 0.01). Conclusion. Higher dietary quality indices associated with lower odds of rCKD in Taiwanese RTRs. Particularly, a positive association between higher intake of red meat and processed meat and higher odds of rCKD was remained exist after transplantation in Taiwanese RTRs. Further dietary guidelines and individualize dietary education were necessary for RTRs to prevent graft function deterioration.